Journal of Parasitic Diseases - Tandon, Veena; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer.)
The primary constituency of the Journal of Parasitic Diseases is parasitology. It publishes original research papers (pure, applied and clinical), which contribute significantly to any area of parasitology. Research papers on various aspects of cellular and molecular parasitology are welcome.
Keywords: Medicine; Health promotion; Infectious diseases; Infectious Diseases; Health Promotion and Disease Prevention; Medicine/Public Health, general